Implementasi Penggunaan Sistem Elektronik, Dan Bukti Potong E-Bupot, Dalam Kemudahan Pelaporan Pajak, Di Dinas Pekerjaan Umum Cipta Karya Dan Tata Ruang Kab. Jember - M. Mirza Pratama; Retno Ayu Wulandari (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to evaluate the effectiveness of implementing an electronic system and digital tax withholding receipts (e-Bupot) in facilitating tax reporting at the Department of Public Works, Human Settlements, and Spatial Planning of Jember Regency. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving employees directly engaged in the tax reporting process. The findings indicate that the e-Bupot system offers significant convenience, such as accelerating the reporting process, reducing errors, and enhancing data accuracy and security. This system replaces the previous manual method, which was time-consuming and prone to mistakes. However, challenges remain, particularly the lack of technical training for users. Overall, the implementation of e-Bupot is considered to support transparency, efficiency, and accountability in government tax administration. The study recommends providing regular training and conducting system evaluations to ensure the sustainability and optimization of e-Bupot implementation.